Understanding Built Environment Proceedings of the National Conference on Sustainable Built Environment 2015 - Seta, Fumihiko; Biswas, Arindam; Khare, Ajay.; Sen, Joy.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book is a comprehensive document visualizing the future of built environment from a multidisciplinary dimension, with special emphasis on the Indian scenario. The multidisciplinary focus would be helpful for the readers to cross-refer and understand others' perspectives. The text also includes case studies substantiating theoretical research. This method of composition helps the book to maintain rational balance among theory, research and its contextual application. The book comprises selected papers from the National Conference on Sustainable Built Environment. The chapters provide varied viewpoints on the core issues of urbanization and planning. This compilation would be of interest to students, researchers, professionals and policy makers.
PART - 1: Land, Housing & Real Estate Accessibility Analysis to Healthcare Infrastructure in Hill Areas: A Case of Shimla -- Conservation of Cultural Heritage: The Necessities, Trends and the Analysis of Current Practices -- Climate Responsiveness of Wada Architecture -- Investigating the Architectural Manifestations of Path and Place in Sacred Sikh Architecture -- Neighbourhood Planning -- Interrelation of Public Open Spaces and Social Behavior: A Chronological Perspective -- Provision of Ecosystem Services through Urban Parks in Mumbai -- Patterns of Flow: The Spatial Dimension of Water in the Desert -- Assessing Impact of Sea Level Rise Along the Coastline of Mumbai City Using Geographic Information System -- Sustainable Landscaping in Cyclone Prone Areas: A Paradigm Shift -- Urban Regeneration and Social Sustainability of Indore City -- Vernacular Architecture: A Sustainable Approach -- Urban Regeneration andSustainability: Importance of Sustainable Transport Systems in the Concept of Eco-City -- Bansal Haveli at Bathinda: Sustainability Paradigm. PART 2: Urban Regeneration & Sustainability Politics of Water and Development: Case of Pune -- The Implementation of Phulkari Embroidery Pattern in Interior Decoration -- Religion Interacts with New Urbanism Holistic City Anandpur Sahib -- A Study on Geometrical Motifs with Special Reference to Old Havelis of Saharanpur -- Assessment of Mughal Mural Decoration on Contemporary Architecture of Agra & Jaipur -- Gender And Space in the Paintings of Raja Ravi Verma & Amrita Sher-Gil -- The Idea of Infinite in Indian and Western Art Perceiving it through the Intangible Cultural Identity -- Local Residents' Perception of Social and Economic Impacts of Urban Riverfront Development: Case of Sabarmati Riverfront Development Project. .
Keywords: Sustainability; Engineering design; Civil engineering; Human geography; Sustainability; Engineering Design; Civil Engineering; Human Geography